[PP.01.17] ADDING HYPERTENSION-RELATED MARKERS OF ORGAN DAMAGE TO RISK SCORE MODELS IMPROVES CARDIOVASCULAR RISK ASSESSMENT: RETROSPECTIVE ANALYSIS OF A LARGE COHORT OF ADULT OUTPATIENTS. (September 2017) - Tocci, G.; Figliuzzi, I.; Presta, V.; Gallo, G.; Costanzi, V.; Attalla, N.; Simonelli, F.; Citoni, B.; Battistoni, A.; Ferrucci, A.; Volpe, M.
Abstract : Objective: Introduction. Global cardiovascular (CV) risk stratification is currently recommended in all adult outpatients in both primary and secondary prevention. Available risk score charts, however, do not include markers of organ damage (OD). Design and method: Aim. To evaluate potential value of adding different markers of hypertension-related subclinical OD to US Framingham, European SCORE and Italian Cuore risk score calculators. Methods: We retrospectically evaluated adult hypertensive outpatients, who underwent blood pressure (BP) assessment and global CV risk stratification at our Hypertension Unit. The following definitions were applied: 1) cardiac OD: electrocardiographic (Sokolow–Lyon index: > 3.5 mV; Cornell Voltage Index: men > 2.4 mV; women > 2.0 mV) or echocardiographic left ventricular (LV) hypertrophy (LV mass index: men > 115 g/m 2 ; women > 95 g/m 2 ); 2) vascular OD: carotid atherosclerotic plaque (>1, 5 mm); 3) renal OD: reduced estimated glomerular filtration rate (eGFR < 60 ml/min/1.73m 2 ) or clearance creatinine (ClCr < 60 ml/min). Different risk score calculators were applied to all included patients. Results: Results. We included an overall population sample of 1, 979 adult outpatients (44.0% female, age 57.2 ± 13.0 years, BMI 26, 6 ± 4, 4 kg/m 2, clinic systolic/diastolic BP 145.4 ± 18.3/85.8 ± 10.7 mmHg), among whom 117 (5.9%) had cardiac, 161 (8.1%) vascular, and 117 (5.9%) renal OD, respectively. US Framingham, European SCORE and Italian Cuore risk scores were all significantly higher in patients with than in those without OD, independently by type and number of OD, as well as age and gender classes. In particular, direct comparisons for US Framingham CVD death, European ESC score and Italian Cuore score showed significantly higher risk in those patients with both ECG-detected LV hypertrophy, ECHO-detected LV hypertrophy, carotid atherosclerosis and reduced eGFR (Figure 4a) or ClCr than in those without the corresponding markers of OD. Conclusions: Conclusions. Presence of cardiac, vascular or renal OD is associated with higher risk scores, independently by type of calculators, age and gender classes. OD detection should be included in individual CV risk stratification aimed at improving diagnostic and therapeutic process.